ANTIOXIDANT AND CYTOTOXICITY PROPERTIES OF ETHYL ACETATE FRACTIONS OF Pandanus tectorius FRUIT AGAINST HELA CELL LINES - Noor Suryani Musa; Nadia Madiha Ramli; Jasnizat Saidin; Yosie Andriani (University of Bengkulu, 2017)
Antioxidant agents play an important role in inhibiting free radical molecules activity thus preventing the cancer disease. This current study aimed to evaluate antioxidant and cytotoxicityproperties of ethyl acetate fractions of Pandanustectorius fruit extract on HeLa cell lines. The radical scavenging activity was measured by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The cytotoxicity was measured by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay against human HeLa cell lines. The result showed that all ethyl acetate fractions of P. tectoriusfruit had high antioxidant property. All of seven fractions of the ethyl acetate extract were observed based on the IC50 value and had high DPPH free radical scavenging activity with the IC50 value range from 0.3 to 2.4 mg/ml compare to positive control,quercetin(IC50= 0.2 mg/ml). Based on the DPPH free radical scavenging activity (antioxidant property), three of seven fractions were chosen for the MTT assay to analyze their cytotoxic activity as anticancer potential agent against HeLa cell lines.From MTT result, one of tree fractions were showed cytotoxicity activity against HeLa cell lines with the IC50value is 12 µg/ml (less than 30 µg/ml), while anothertwo fractions was found not cytotoxic against HeLa cell lines.It is clearly indicated that P. tectoriusfruit has a very good potential as antioxidant and anticancer agent.